P800 Prevalence of curable sexually transmitted infections among refugees: global systematic review and meta-analysis. (14th July 2019) - Mumtaz, Ghina; Sharara, Eman; Dejong, Jocelyn; Sibai, Abla; Roberts, Bayard; Abu-Raddad, Laith
Abstract : Background: The world is witnessing one of the worst refugee crises of all times. Disrupted healthcare systems, limited availability and access to services, poverty, and increased exposure to sexual violence among others increase the vulnerability of populations in humanitarian settings to poor sexual/reproductive outcomes, including sexually transmitted infections (STIs). Our objective is to characterize, for the first time, the epidemiology of curable STIs - Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Treponema pallidum (syphilis), and Trichomonas vaginalis (TV) - among refugees and internally displaced populations globally, and to estimate their pooled mean prevalence. Methods: We conducted a PRISMA-guided systematic review of literature through PubMed and Embase databases, and of abstracts of international HIV/STI conferences, with no language/time restrictions. Pooled prevalence of current and/or lifetime infection for each STI was estimated using random-effects meta-analyses. Results: We identified 37 eligible studies that contributed 103 STI prevalence measures for 935, 191 refugees. The majority of studies were for syphilis (65%), whereas CT, NG, and TV accounted for 14%, 18%, and 4% of total measures, respectively. African and South-east Asian refugees were represented the most. Only one study was conducted among Syrian refugees - currently the largest refugee population worldwide. Pooled prevalence of current infection was 1.6% (95% CI: 1.2–2.1%) for syphilis, 0.6% (95% CI: 0.1–1.4%) for NG, 0.5% (95% CI: 0.2–1.0%) for CT, and 29.3% (95% CI: 21.3–38.0%) for TV. The latter included mostly symptomatic populations. Pooled prevalence of lifetime syphilis infection was 3.3% (95I CI: 1.5–5.8%). Conclusion: Despite the identified studies, there is a large knowledge gap for these infections in this population. Findings suggest overall comparable prevalence levels to the general population. However, further studies are needed to better understand the recent burden of STIs and the sexual health needs of affected populations in different global settings, to inform screening and treatment policy and programming. Disclosure: No significant relationships.